2017
DOI: 10.1155/2017/6215136
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance ofSalmonella entericaSerovars Typhi and Paratyphi Isolates from a General Hospital in Karawaci, Tangerang, Indonesia: A Five-Year Review

Abstract: Typhoid and paratyphoid fever known as enteric fever pose important global public health problem, with 21.6 million cases and approximately 250,000 deaths annually. It is a prevalent disease in Indonesia, but data on the antimicrobial resistance pattern is limited. This study aim was to provide data on the antimicrobial resistance pattern of S. Typhi and S. Paratyphi bloodstream isolates in a general hospital in Karawaci, Tangerang, Banten, Indonesia, during the period of January 2011 to December 2015. Suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Contrary to this, FQNS was high amongst S. Paratyphi A in South Asia, with a pooled prevalence above 90% for 2000–2004, 2005–2009 and 2010–2014 (only one study available prior to 2000; Table 3, Additional file 1: Figure S12). Only three studies from Southeast Asia were identified; two from Indonesia [72, 73] found no FQNS and one from Cambodia [74] found 11% (183 isolates) FQNS S. Paratyphi A (Additional file 1: Figure S13). All six studies from East Asia were from 2004 onwards and found very high levels of FQNS in S. Paratyphi A (Additional file 1: Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to this, FQNS was high amongst S. Paratyphi A in South Asia, with a pooled prevalence above 90% for 2000–2004, 2005–2009 and 2010–2014 (only one study available prior to 2000; Table 3, Additional file 1: Figure S12). Only three studies from Southeast Asia were identified; two from Indonesia [72, 73] found no FQNS and one from Cambodia [74] found 11% (183 isolates) FQNS S. Paratyphi A (Additional file 1: Figure S13). All six studies from East Asia were from 2004 onwards and found very high levels of FQNS in S. Paratyphi A (Additional file 1: Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…The trend of resistance to a growing number of antimicrobial classes is alarming, including recently to azithromycin 37 , 54 , 55 and outbreaks of XDR Salmonella Typhi. 12 – 14 Our review captured one study in Pakistan 36 and one in Indonesia 56 reporting meropenem resistance in Salmonella Typhi. To our knowledge, these would be the first reports of carbapenem resistance in Salmonella Typhi and cause for great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to different antibiotics has increasingly been reported in bacteria isolated from animals and humans and has become an important global issue. In particular, there is widespread dissemination of antimicrobial‐resistant strains among S. enterica (Hardjo Lugito & Cucunawangsih, ; Yang et al, ). Our susceptibility tests revealed the Salmonella isolates obtained from eggs were highly resistant to β‐lactams antibiotic, especially ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…This serotype was also the most widespread in our study ( Figure 1). Serotype Typhi is defined as often being resistant to some first-line recommended antibiotics (Hardjo Lugito & Cucunawangsih, 2017). There are 11 serovars found in our Salmonella isolates.…”
Section: Discussionmentioning
confidence: 99%